2021
DOI: 10.1108/ijem-04-2020-0203
|View full text |Cite
|
Sign up to set email alerts
|

Goals of the national mathematics curriculum of Pakistan: educators’ perceptions and challenges toward achievement

Abstract: PurposeThe national mathematics curriculum of Pakistan has emphasized on improving content knowledge, reasoning abilities and problem-solving skills of students about thinking, communicating and solving mathematics (national mathematics curriculum of Pakistan, 2006). Whereas, there is a need to understand the point of view of teachers about the challenges they face in achieving the goals of national mathematics curriculum. This will help leading teacher training institutions to revisit their math teacher conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Pakistan's national curriculum actually focused on the content of mathematics and emphasized mental qualities: mathematical reasoning, problem solving and communication. However, the function is still awaited to achieve the target structure of its documented form (Mughal et al, 2021).Mathematics content is not fixed in nature and there are different points of view. The way the teacher transfer it makes it either absolute or fallibilist.…”
Section: Philosophy Behind the Mathematical Content Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Pakistan's national curriculum actually focused on the content of mathematics and emphasized mental qualities: mathematical reasoning, problem solving and communication. However, the function is still awaited to achieve the target structure of its documented form (Mughal et al, 2021).Mathematics content is not fixed in nature and there are different points of view. The way the teacher transfer it makes it either absolute or fallibilist.…”
Section: Philosophy Behind the Mathematical Content Developmentmentioning
confidence: 99%
“…One of the basic problems in Pakistan regarding the problem of primary mathematics is the lack of specific content of primary teacher for this job. Mughal et al (2021) clearly indicated that the majority of primary school teachers faced difficulties in delivering the content along with concept in most of the basic mathematics. Further teachers also faced difficulties in using hands and minds-on-activities.…”
Section: Problems In the Implementation Of Mathematics Curriculummentioning
confidence: 99%
“…In the Pakistani context, various approaches have been deployed to improve and measure students' mathematics achievements; total quality management (Mahmood & Ismail, 2018), metacognition (Habib & Rana, 2020), the effect of ICT (Ishaq et al, 2020;Khan, 2020), the influence of physical facilities (Arshad et al, 2018), executive functioning (Hania et al, 2019), parental influence (Ahmed et al, 2019), the effect of cooperative learning (Atiq et al, 2021) and problemsolving (Ahmad et al, 2022). Even then, students' mathematics results are still unsatisfactory (Mughal et al, 2021;Ullah et al, 2018). There is a need to find any practical approach that is costeffective and easy to use in classrooms to enhance their mathematics performance.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Most public schools in the government still employ more conventional teaching approaches (Zhongming, Linong, Xiaona, Wangqiang, & Wei, 2019). Government schools have the lowest ratings for the quality of education (Mughal, Asad & Adams, 2020). The students' negative attitudes about mathematics are the root reason for their academic failure (Mazana, Suero Montero, & Olifage, 2019).…”
Section: Introductionmentioning
confidence: 99%